How useful is a history of rubella vaccination for determination of disease susceptibility? A cross-sectional study at a public funded health clinic in Malaysia - Cheong, Ai Theng; Tong, Seng Fah; Khoo, Ee Ming (BioMed Central, 2013)
Background: Identification of pregnant women susceptible to rubella is important as vaccination can be given postpartum to prevent future risks of congenital rubella syndrome. However, in Malaysia, rubella antibody screening is not offered routinely to pregnant women in public funded health clinics due to cost constraint. Instead, a history of rubella vaccination is asked to be provided to establish the women’s risk for rubella infection. The usefulness of this history, however, is not established. Thus, this paper aimed to determine the usefulness of a history of rubella vaccination in determining rubella susceptibility in pregnant women. Methods: A cross-sectional study was conducted on 500 pregnant women attending a public funded health clinic. Face-to-face interviews were conducted, and demographic data and history of rubella vaccination were obtained. Anti-rubella IgG test was performed. Results: A majority of the women (66.6%) had a positive vaccination history. Of these, 92.2% women were immune. A third (33.4%) of the women had a negative or unknown vaccination history, but 81.4% of them were immune to rubella. The sensitivity and specificity of a history of rubella vaccination in identifying disease susceptibility was 54.4% (95% CI: 40.7, 67.4%) and 69.3% (95% CI: 64.7, 73.5%) respectively; the positive predictive value was 18.6% (95% CI: 13.1, 25.5%) and the negative predictive value was 92.2% (95% CI: 88.6, 94.7%). Conclusions: A vaccination history of rubella had a poor diagnostic value in predicting rubella susceptibility. However, obtaining a vaccination history is inexpensive compared with performing a serological test. A cost-utility analysis would be useful in determining which test (history versus serological test) is more cost-effective in a country with resource constraint.